One political economy, one competitive strategy? comparing pharmaceutical firms in Germany, Italy, and the UK - Herrmann, Andrea M. (Oxford : Oxford University Press, 2008)
This text examines how firms adapt to the pressures of increasing international competition by testing the arguments on 'strategy specialization' proposed in the competitiveness literature in general, and by contributors to the 'varieties of capitalism' debate in particular.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Pharmaceutical industry -- Germany; Pharmaceutical industry -- Italy; Pharmaceutical industry -- Great Britain